Superhighways and the future of public services and citizenship in the information age - Taylor, John (Uporabna informatika (Ljubljana), 1996)
In the information age it is imperative that public service providers, on the one hand, and telecommunications operators, on the other, identify the need to integrate their activities. For the public service provider this will open the way for proper strtegic and operational planning of electronic services delivery. For the telecommunications operator will secure a better understanding of market demand for enhanced infrastructure provision as well as bringing forward the question of how the cost of such infrastructure investments should be met.
Keywords: informacisjki sistemi; javni servis; načrtovanje; telekomunikacije